The Role of Hypoxia Inducible Factor (HIF) 1α in the Pathogenesis of Liver Cirrhosis: A Narrative Literature Review - Sari, Anita Revera; Suyata (HM Publisher, 2024)
The small changes in oxygen tension that occur during viral hepatitis, metabolic disorders, steatohepatitis, inflammation, and carcinogenesis are sufficient to increase hypoxic response, namely an increase in HIF. HIF is a protein that belongs to the PAS (period circadian protein-aryl hydrocarbon receptor nuclear translocator-single-minded protein) family. HIF regulates the adaptation of cells to oxygen. HIF is a transcription factor containing α and β subunits. The expression of the α subunit is oxygen-dependent, while the β subunit is expressed continuously and independently of oxygen. HIFs regulate various signaling events by binding to specific DNA sequences known as hypoxia response elements (HREs) in target genes, leading to an increase or decrease in their transcription. HIF-1α is a key regulator of hypoxia signaling.